Discriminating bovine mastitis pathogens by combining loop-mediated isothermal amplification and amplicon-binding split trehalase assay - Miao, Zhuohan; De Buck, Jeroen (Frontiers in Veterinary Science, 2024)
Bovine mastitis is predominantly caused by intramammary infections with various Gram-positive and Gram-negative bacteria, requiring accurate pathogen identification for effective treatment and antimicrobial resistance prevention. Here, a novel diagnostic method was developed to detect mastitis pathogens in milk samples by combining loop-mediated isothermal amplification with a split enzyme biosensor whereby trehalase fragments were fused with a DNA-binding protein, SpoIIID. Three primer sets, LAMPstaph, LAMPstrep, and LAMPneg, harboring SpoIIID recognition sequences targeted Staphylococcus, Streptococcus, and Gram-negative pathogens, respectively. Limits of detection were determined for DNA extracted from bacterial culture and bacteria-spiked milk. The combined method detected as low as 2, 24, and 10 copies of genomic DNA of staphylococci, streptococci and Escherichia coli and 11 CFU/ml for milk spiked with Escherichia coli. Higher detection limits were observed for Gram-positive bacteria in spiked milk. When testing genomic DNA of 10 mastitis isolates at concentrations of 106 and 103 copies per reaction, no cross-reactivity was detected for LAMPstaph nor LAMPstrep, whereas the LAMPneg assay cross-reacted only with Corynebacterium sp. at the highest concentration. This combined method demonstrated the potential to distinguish mastitis pathogenic Gram types for a rapid decision of antimicrobial treatment without culturing.